The Mysterious Multitude: Structural Perspective on the Accessory Subunits of Respiratory Complex I - Padavannil, Abhilash; Ayala-Hernandez, Maria G.; Castellanos-Silva, Eimy A.; Letts, James A. (Frontiers in Molecular Biosciences, 2022)
Complex I (CI) is the largest protein complex in the mitochondrial oxidative phosphorylation electron transport chain of the inner mitochondrial membrane and plays a key role in the transport of electrons from reduced substrates to molecular oxygen. CI is composed of 14 core subunits that are conserved across species and an increasing number of accessory subunits from bacteria to mammals. The fact that adding accessory subunits incurs costs of protein production and import suggests that these subunits play important physiological roles. Accordingly, knockout studies have demonstrated that accessory subunits are essential for CI assembly and function. Furthermore, clinical studies have shown that amino acid substitutions in accessory subunits lead to several debilitating and fatal CI deficiencies. Nevertheless, the specific roles of CI’s accessory subunits have remained mysterious. In this review, we explore the possible roles of each of mammalian CI’s 31 accessory subunits by integrating recent high-resolution CI structures with knockout, assembly, and clinical studies. Thus, we develop a framework of experimentally testable hypotheses for the function of the accessory subunits. We believe that this framework will provide inroads towards the complete understanding of mitochondrial CI physiology and help to develop strategies for the treatment of CI deficiencies.